Myocardial Extracellular Volume Fraction and Change in Hematocrit Level: MR Evaluation by Using T1 Mapping in an Experimental Model of Anemia - Kim, Pan Ki; Hong, Yoo Jin; Sakuma, Hajime; Chawla, Ashish; Park, Jeffrey Kihyun; Park, Chul Hwan; Hong, Donghyun; Han, Kyunghwa; Lee, Ji Yeon; Hur, Jin; Lee, Hye-Jeong; Kim, Young Jin; et al. (Radiology, 2018)
Purpose To evaluate the effect of changes in hematocrit level on myocardial extracellular volume (ECV) fraction, as quantified with cardiac magnetic resonance (MR) imaging in an animal model. Materials and Methods Thirteen adult male Sprague-Dawley rats underwent cardiac MR imaging before and after induction of anemia. MR imaging procedures, including unenhanced and contrast material-enhanced T1 mapping, were performed by using a saturation recovery Look-Locker sequence with a 9.4-T unit. An optimized T1 mapping sequence was established in the phantom study. Systolic function of the left ventricle (LV) was calculated from the cine images. Native and postcontrast T1 values of the LV myocardium at the midcavity level and LV blood pool, partition coefficients, and ECV were calculated. Histopathologic examination of the heart was performed after sacrifice. Intergroup comparison of variables was performed with the paired t test. Results The postanemia models exhibited lower hematocrit levels, postcontrast T1 values of the LV pool, and partition coefficients (mean, 45.7% ± 5.2 [standard deviation]; 563.8 msec ± 155.7; and 29.2 ± 3.5, respectively) than did the preanemia models (mean, 59.0% ± 4.1; 690.2 msec ± 109.7; and 38.2 ± 4.4, respectively) (P < .05 for all comparisons). There were no differences between the pre- and postanemia groups in terms of LV ejection fraction (mean, 72.7% ± 2.1 vs 73.2% ± 4.7; P = .78) and ECV (mean, 15.5% ± 2.0 vs 16.0% ± 1.9; P = .24). Conclusion Myocardial ECV measured with contrast-enhanced T1 mapping cardiac MR imaging did not significantly change despite changes in hematocrit level in anemic rat models. Extrapolation of this finding from animal models to human subjects suggests that ECV measured with MR imaging could be a robust parameter in anemic patients.